A Critical Analysis of Cultural Representation in the Korean Language Textbooks Published in Korea and Used in Thailand - Ki Young Choi; Dong Bae Lee (SAGE Open)
This research evaluates the representation of Korean cultural values and ideologies in Korean language textbooks published in Korea and utilised by Thai universities, as well as Thai students’ reactions to these portrayals. Through in-depth textual and visual analysis employing critical discourse analysis (CDA) and visual image analysis (VIA), prevalent themes, including morality, etiquette, and food culture, were identified. The results indicate that these textbooks frequently idealise and oversimplify Korean culture, cultivating a favourable perspective consistent with cultural imperialism. To complement the discourse and visual analysis, semi-structured interviews with Thai university students were conducted to explore their interpretations and reactions. Findings from these interviews reveal that Thai students critically evaluated these portrayals, informed by their own cultural backgrounds and exposure to external media. This study highlights the necessity for textbooks to represent cultural diversity accurately, avoid stereotypes, and incorporate both source and target cultural perspectives. The results demonstrate that cultural understanding can develop independently through media and other resources, independent of formal instruction. Recommendations are offered for more inclusive textbook design and supplemental resources to address these issues.